The Impact of Empowering Leadership and Work Engagement on the Performance of Functional Officials - Achmad Hardiansyah; Wa Ode Zusnita Muizu; Yunizar Yunizar (Budapest International Research and Critics University, 2022)
The performance of functional officials is one of the government's keys to improving the performance of the organization. Empowering leadership and work engagement in functional officials are things that are indicated to affect the performance of functional officials. This study aims to examine and analyze the impact of empowering leadership and work engagement on the performance of functional officials. Respondents in this study were 180 functional officials within the Secretariat General of the Ministry of Finance. Data were obtained by distributing questionnaires to functional officials. This study uses an explanatory survey method with path analysis. The results of this study indicate that empowering leadership and work engagement have a significant impact on the performance of functional officials.